2018
DOI: 10.15517/rbt.v66i2.33410
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest remnants as shelters of avian diversity within a tourism development matrix in Yucatan Peninsula, Mexico

Abstract: Tropical forests have undergone extensive transformation because of increasing tourism development, in addition to historic clearing for agricultural and cattle grazing activities. Altogether, these activities have had an important effect on bird diversity, reducing the habitat available to many species. In this study, the role of tropical forest remnants located between different land use types was evaluated for species diversity, composition, and distribution of the bird community at Akumal region in Quintan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
0
0
1
Order By: Relevance
“…35 Moreover, a study in the Yucatan Peninsula, Mexico has shown that mature and fragmented forests have a higher number of bird species than the surrounding mosaic-modified landscape, such as golf courses and agricultural fields. 36…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, a study in the Yucatan Peninsula, Mexico has shown that mature and fragmented forests have a higher number of bird species than the surrounding mosaic-modified landscape, such as golf courses and agricultural fields. 36…”
Section: Discussionmentioning
confidence: 99%
“…Si bien la avifauna de la RBSAT incluye un alto porcentaje de especies residentes permanentes, presenta un importante componente de especies migratorias, lo que destaca la función que tiene la reserva como hábitat para este tipo de aves. El patrón encontrado es similar al registrado en selvas bajas caducifolias de la región de Tomatlán, Jalisco (Ramírez-Albores, 2007), en la cañada del río Sabino en Oaxaca (Vázquez y col., 2009) y para algunos parches remanentes de selva baja caducifolia en la península de Yucatán (Ramírez-Albores y Pérez-Suárez, 2018).…”
Section: Trabajo De Campo Y De Gabineteunclassified